Is Loan Shark an Alternative? The Intentions to Take a Loan from Loan Sharks in Indonesia - Safwan Kamal; Muslem Muslem; Mulyadi Mulyadi; Erne Suzila Kassim; Muhammad Uzair Zulkifly (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Research rarely reaches the discussion of loan sharks. This study describes how intentions are influenced by service, word-of-mouth, and subjective norms, with knowledge of usury acting as a moderating variable. This quantitative study involved 150 respondents. The data collected was analyzed by using structural Equation Modeling (SEM) with SmartPLS 3 Software. According to this study, service significantly affected intention to take a loan from loan sharks but had no influence on word-of-mouth. Though it has no influence on intention, the subjective norm has a significant influence on word-of-mouth. The service on the intention is mediated by word of mouth, which has an influence on the intention. However, word-of-mouth does not act as a mediating variable between subjective norms and intentions. The intention to use the services of loan sharks is significantly moderated by knowledge about usury, which also significantly moderates word-of-mouth and subjective norms. It did not, however, moderate the influence of service on intentions. As a result, it is recommended that the government create Islamic financial institutions not only for the middle class and upper class but also for the lower economic class, which is vulnerable to loan sharks.